2002
DOI: 10.1021/jf0108718
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipid Composition on Meat-like Model Systems Containing Cysteine, Ribose, and Polyunsaturated Fatty Acids

Abstract: This paper compares the volatile constituents of model systems containing the important meat aroma precursors cysteine and ribose, with and without either methyl linoleate, an n-6 fatty acid, or methyl alpha-linolenate, an n-3 acid, both of which are present in meat. Many of the volatile compounds formed from the reaction between cysteine and ribose were not formed, or formed in lower amounts, when lipid was present. This may be due to the reaction between hydrogen sulfide, formed from the breakdown of cystein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
95
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(103 citation statements)
references
References 26 publications
7
95
0
1
Order By: Relevance
“…Interactions between Maillard reaction products and lipids have been extensively studied in model systems (Elmore et al, 2002;Pan et al, 2011). These investigations included analyses of the course of cysteine and ribose interactions with various types of fat.…”
Section: Formation Of Volatile Compounds In Meat and Meat Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interactions between Maillard reaction products and lipids have been extensively studied in model systems (Elmore et al, 2002;Pan et al, 2011). These investigations included analyses of the course of cysteine and ribose interactions with various types of fat.…”
Section: Formation Of Volatile Compounds In Meat and Meat Productsmentioning
confidence: 99%
“…thiophenes and furans. Due to their high reactivity, they increase the levels of fatty acids degradation products, of n-6 and n-9 families, which in turn affects the final flavor of heat-treated meat products (Elmore et al, 2002). During the heating of cysteine, ribose and lecithin, changes were observed in the volatile compounds formed, i.e.…”
Section: Formation Of Volatile Compounds In Meat and Meat Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in off-flavour intensity ratings may be associated with lower proportions of n-3 PUFA in LT when feeding DDGS. Overall, PUFA have been related to off flavours in beef, but these are typically associated with the oxidation products of n-3 PUFA because they have more Mapiye, Aalhus, Turner, Vahmani, Baron, McAllister, Block, Uttaro and Dugan double bonds and are more readily oxidised compared with n-6 and n-9 PUFA (Elmore et al, 2002). It should be noted, however, that absolute changes in sensory attributes were small (<1 panel unit) and would not likely be detectable by the untrained consumer.…”
Section: Sensory Attributesmentioning
confidence: 99%
“…Changes to the firmness of intramuscular fat can then affect meat tenderness (Wood, 1990). In fact, Elmore et al (2002) and Miller (2001) indicated there is a desire to increase the PUFA in meat for human health benefits. However, when PUFA are too abundant, the oxidation developed can result in a shorter shelf life and negative flavors or off-flavors in cooked meat.…”
mentioning
confidence: 99%